L’information médicale au Maroc : Le journalisme face à ses contraintes - Salaheddine Lemaizi (L’Année du Maghreb)
Between the communicators with consequent means, deployed to influence the message of professional of information in their favour; and the draftings in a position of low manpower and under-investment in a journalism of quality, the journalist found himself as “circular circulation of information”. By peeling the mechanisms of contact and influence of communicators of the pharmaceutical sector in Morocco, the main goal is to understand the opposite strategies of actors belonging to the world of the media. Each actor wants to impose his agenda and his priorities. Despite these external and internal constraints, the journalists have maneuver margins which they use to escape the shaping from information by the communicating ones.